KEBERTAHANAN TARI REJANG SUTRI DI DESA BATUAN KECAMATAN SUKAWATI KABUPATEN GIANYAR (Perspektif Sat Cit Ananda) - I Made Sukariawan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Rejang Sutri dance is different from other Rejang dances. The Rejang Sutri dance in Batuan Village, Sukawati District, Gianyar Regency has uniqueness that does not exist in other villages, this dance is specially performed at the beginning of the Sasih Kelima to the end of Sasih Kesanga at Pengrupukan and danced by women who live in environment of Batuan Village, Sukawati Gianyar. The dancers have no age limit, have links to Hinduism and are the cultural identity of Batuan Village. In addition, the Rejang Sutri dance is a form of community appreciation of one of the manifestations of Ida Sang Hyang Widhi Wasa / God. Traditionally, the Rejang Sutri dance has survived to this day. This research is entitled: Resilience of Rejang Sutri Dance in Batuan Village, Sukawati District, Gianyar Regency (Sat, Cit, Ananda Perspective).The problems studied namely Why is the Rejang Sutri Dance in Batuan Village, Sukawati District, Gianyar Regency still surviving, Who contributed to maintaining Rejang Sutri Dance in Batuan Village, Sukawati District, Gianyar Regency, How do you maintain Rejang Sutri Dance in Batuan Village, Sukawati District, Gianyar Regency. The above problems will be examined using several theories. The theories used are religious theory, structural functional theory, and constructive education theory. In addition, in obtaining and analyzing data, several methods are used, namely the method of observation, interviews and document study. This type of research is qualitative and described by descriptive methods, in order to obtain a comprehensive conclusion.Based on the results of the analysis and discussion of the results of the research, it can be concluded as follows: (1) The persistence of the Rejang Sutri dance in Batuan Village is inseparable from the beliefs of the people of Batuan Village and making the Rejang Sutri dance34Vol. 11 No. 1 Maret 2021as Sradha Bhakti for the people of Batuan Village where the relationship of belief in God is true truth or Sat or Satyam which is manifested in the form of sacred offerings, namely the Rejang Sutri dance, the people of Batuan Village believe that by making art an offering and its yadnya to get closer to God (Ida Sang Hyang Widhi Wasa). In accordance with the basis of Hindu religious beliefs known as Srada which consists of five parts, namely Panca Srada. One of these srada which is closely related is the first srada, namely believing in the existence of Brahman. The people of Batuan Village believe that the performance of the Rejang Sutri dance is a means of offering that can reject reinforcements or ward off disease outbreaks. So that the Rejang Sutri dance still survives because it embraces Sat or Satyam which means true truth.(2) Contributing to the survival of the Rejang Sutri dance in Batuan Village is Prajuru Desa Adat Batuan as a supporter of the Rejang Sutri dance, which in an effort to preserve the Rejang Sutri dance has been contained in the Awig-awig of Batuan Traditional Village and has become an agreement with all Krama Batuan Traditional Village and its members. the community as supporters of the Rejang Sutri dance in its sustainability. Because the Rejang Sutri dance is a cultural heritage of sacred arts in Batuan Village. So with the performance of the Rejang Sutri dance in Batuan Village, the people of Batuan Village have supported the sustainability of the Rejang Sutri dance as a sacred and sacred offering that places Siwam or Cit which means purity, honesty, honesty as very important things and cannot be separated from Satyam or Sat who meaning true truth as well as related to Sundaram or Ananda which means beauty, happiness which the people of Batuan Village manifest in the Rejang Sutri dance performance.(3) The way to maintain the Rejang Sutri dance in Batuan Village is by means of inheritance from generation to generation because the Rejang Sutri dance contains aspects of repelling reinforcements, aspects of ritual / ceremony, and aspects of beauty related to movement, composition, costumes, arenas and aspects of happiness in survival. Rejang Sutri dance where the people of Batuan Village still maintain the Rejang Sutri dance because it is closely related to aspects of Satyam or Sat (truth), Siwam or Cit (holiness) and Sundaram or Ananda (beauty / happiness). Because in sacred offerings towards the truth a happiness is achieved from the people of Batuan Village, so that they live in safety, prosperity and peace.